Impacto dos laudos de homicídio de latrocínio junto aos operadores do direito e às sentenças judiciais: o caso da perícia criminal do Instituto de Criminalística no âmbito do Distrito Federal - Gonçalves, Marcelo Nunes (2013)
This research aims to identify the role of the Report of Criminal Expertise with the law operators as well as the rate of participation in the judgments in court procedures. It is known that the Report of Criminal Expertise is a document of technical - scientific nature – produced by forensic scientist – with the aim of assisting the courts with their content ba sed on the study of experts. As a help to J ustice, the Report of Criminal Expertise is the most robust evidence used by the magistrate s to issue a court order or for the use of juries in cases of crimes against life. Part of the research method was qualita tive and, for data collection,we used interview - by questionnaire - with law enforcement officers (police officers, judges and prosecutors) who acted in cases of murder and/or robbery and work in the five Administrative Regions that covered over 50% of th ese crimes. Later the documental analysis was begun, in which were verified 1 72 (one hundred seventy - two ) site surveys and its repercussions in the judicial. Some conclusions regarding the Reports have been suggested, such as their lateness in some cases. But it was possible to take a new look at the tech nical document that both aid in the C riminal J ustice. Was discussed, also, the lack of feedback information for forensic experts from the Crime Lab, which causes problems of motivational order .